Functional specificity of the homeodomain protein fushi tarazu: the role of DNA-binding specificity in vivo. - Schier, A F (1993)
The mechanisms determining the functional specificity of Drosophila homeodomain proteins are largely unknown. Here, the role of DNA-binding specificity for the in vivo function of the homeodomain protein fushi tarazu (ftz) is analyzed. We find that specific DNA binding is an important but not sufficient determinant of the functional specificity of ftz in vivo: The ftz DNA-binding specificity mutant ftzQ50K retains partial ftz wild-type activity in gene activation and phenotypic rescue assays. Furthermore, specificity mutations in a ftz-in vivo binding site only partially reduce enhancer activity as compared to null mutations of this site. Despite bicoid-like DNA-binding specificity ftzQ50K does not activate natural or artificial bcd target genes in the realms of ftz. These results are discussed in the light of recent observations on the mechanism of action of the yeast homeodomain protein alpha 2.